Interfacial interaction enhancement by shear-induced β-cylindrite in isotactic polypropylene/glass fiber composites. (25th September 2016) - Qin, Yijing; Xu, Yahu; Zhang, Liying; Zheng, Guoqiang; Yan, Xingru; Dai, Kun; Liu, Chuntai; Shen, Changyu; Guo, Zhanhu
Abstract: Isotactic polypropylene (iPP)/glass fiber (GF) composites with different specific interfacial features ( viz ., α-spherulite, α-cylindrite and β-cylindrite) were prepared via shear-induced interfacial crystallization. α-spherulite, α-cylindrite and β-cylindrite were successively encouraged at the interface between iPP matrix and GF with increasing the fiber-pulling speed. Moreover, the composite specimens containing β-cylindrite exhibited remarkably higher interfacial shear strength (IFSS) than those containing α-spherulite or α-cylindrite, as demonstrated by the single fiber fragmentation test (SFFT). More interestingly, simultaneously improved tensile strength and toughness were observed in the presence of β-cylindrite. This study offers a new insight that β-cylindrite produced by shear is an alternative approach to achieve comprehensive mechanical properties for the iPP/fiber composite systems. Graphical abstract: Highlights: Different specific interfacial features in iPP/GF composites were prepared. β-Cylindrite resulted in the highest interfacial shear strength (IFSS). Tensile strength and toughness were simultaneously improved due to β-cylindrite.